Implementation of DSN-MUI Fatwa No. 123 of 2018: Optimizing the Management of Funds that Should Not Be Recognized as Income in Sharia Financial Institutions - Rifai, Ahmad; Sunaryo Mukhlas, Oyo (Zona Law And Public Administration Indonesia, 2025)
This study aims to analyze the implementation of DSN-MUI Fatwa No. 123 of 2018 concerning the optimization of fund management that should not be recognized as income in Islamic financial institutions (LKS). This fatwa is an important instrument in maintaining sharia compliance and preventing the mixing of halal and non-halal funds in the operation of LKS. This study uses a qualitative approach with a case study method in several selected LKS. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. The results show that most of the LKS have separated and recorded non-revenue funds administratively, but systemic implementation still faces various challenges, such as limited human resources, technological infrastructure, and the absence of uniform technical reporting standards. However, there are optimization efforts through the formation of SOPs, collaboration with Islamic social institutions, and the integration of supervisory functions by DPS. This research shows that the implementation of fatwas not only demands formal compliance, but also requires a sustainable transformation of governance and social accountability. These findings are expected to contribute to strengthening regulations and improving the quality of Islamic financial practices in Indonesia